LEGAL PROTECTION FOR SHARE TRANSFERS: THE ROLE OF DERIVATIVE ACTION LAWSUITS IN DEFENDING SHAREHOLDER RIGHTS - Asih, Ayu Lestarining; Abdullah, Ali (Jurnal Ilmiah Advokasi, 2025)
This research examines the legal complexity of share transfer in Indonesia, focusing on derivative action as an instrument for protecting shareholders' rights. This research is strictly limited to the Indonesian legal framework and does not involve comparative analysis with foreign jurisdictions. The methodological scope is also limited to a normative juridical approach, relying solely on statutory analysis, doctrinal studies, and jurisprudence without conducting empirical data collection or field-based validation. The study aims to analyze the legal construction of share transfer, identify juridical challenges, and evaluate the effectiveness of derivative action in protecting minority shareholders' interests. Utilizing a normative juridical method, the research investigates legislation, legal literature, and relevant jurisprudence. Findings reveal that derivative action is a complex legal mechanism transforming corporate governance, providing space for minority shareholders to protect corporate interests from potential abuse. The research uncovers significant implementation challenges, including evidence complexity and structural resistance. The conclusion emphasizes the need for regulatory framework improvement, strengthening judicial institutions' capacity, and enhancing legal literacy to create an effective and just legal protection system.Keywords: Share Transfer, Derivative Action, Legal Protection